Peace: a history of movements and ideas - Cortright, David (Cambridge University Press, 2008)
1. What is peace? Idealism and realism ; New wars ; Defining terms ; What's in a word? ; "Pacifist" Japan? ; Latin American and African traditions ; Pacifism and "just war" ; An outline of peace history ; An overview of peacemaking ideas -- Part I. Movements. 2. The first peace societies ; Stirrings ; Social origins and political agendas ; Elihu Burritt : the learned blacksmith ;The first peace congresses ; The right of self-determination ; Universalizing peace ; The Hague Peace Conference ; Not enough -- 3. Toward internationalism. Concepts and trends ; The arbitration revolution ; A League of Nations ; Wilson's vision ; The challenge of supporting the League ; Outlawing war -- 4. Facing fascism. Peace movement reborn ; Pledging war resistance ; Revolutionary antimilitarism ; The Peace Ballot ; Against appeasement ; Imperial failure ; The neutrality debate ; The emergency peace campaign ; Losing Spain ; The end of "pacifism" -- 5. Debating disarmament. Early reluctance ; Disarmament to the fore ; Challenging the "merchants of death" ; The naval disarmament treaties ; World disarmament conference ; The collapse of disarmament ; Disarmament at fault? -- 6. Confronting the cold war. Creating the United Nations ; The rise of world federalism ; Cold war collapse ; Militarization and resistance in Japan ; The leviathan ; Speaking truth to power -- 7. Banning the bomb. The shock of discovery ; Scientists organize ; The Baruch plan ; For nuclear sanity ; The beginning of arms control ; Nuclear pacifism in Japan ; The rise of the nuclear freeze ; God against the bomb ; A prairie fire ; Ferment in Europe ; Who won? ; Lessons from the end of the cold war -- 8. Refusing war. Vietnam : a triangular movement ; Challenging presidents, constraining escalation ; Social disruption and political costs ; Resistance in the military ; The rise of conscientious objection ; The movement against war in Iraq ; Winning while losing ; Countering the "war on terror” --